Use of IRAMUTEQ software in qualitative research: an experience repor - Fernanda Garcia Bezerra Góes; Andressa Silva Torres dos Santos; Brenda Lucas Campos; Aline Cerqueira Santos Santana da Silva; Liliane Faria da Silva; Luiz Carlos Moraes França (Universidade Federal de Santa Maria, 2021)
Objective: to report the experience of using the software Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires (IRAMUTEQ) as a computerized tool to support the analysis of textual data in qualitative research in health. Method: this was an experience report that took place between March and June 2019, based on qualitative research developed through the Creative-Sensitive Method and using IRAMUTEQ. Newborns and family members of newborns from a public hospital located in the city of Rio das Ostras in the state of Rio de Janeiro, Brazil, participated in the study. Results: it was possible to verify that the different lexical analysis techniques available in IRAMUTEQ allowed to discriminate the semantic contents referring to the caregivers' claims about the care to be performed with the newborn at home. Conclusion: this computerized tool proved to be useful, adequate, and reliable, qualifying the textual analysis process.